2010
DOI: 10.1007/s11060-010-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bevacizumab in active brain metastases from non-small cell lung cancer

Abstract: Background-Bevacizumab is effective for the treatment of non-small cell lung cancer (NSCLC). Ongoing trials are exploring the safety of bevacizumab in patients with inactive, previously treated brain metastases. However, bevacizumab safety and efficacy in the treatment of active brain metastases is unknown. Bevacizumab received accelerated FDA approval for progressive glioblastoma, a primary brain tumor, because of high response rates and low incidence of intracranial hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 14 publications
(17 reference statements)
0
58
0
1
Order By: Relevance
“…The PASSPORT study of patients with non-small lung cell carcinoma (NSCLC) and nonprogressive brain metastases after RT demonstrated that bevacizumab in addition to chemotherapeutic agents or erlotinib did not induce grade 2 ICH and that bevacizumab can be safely used in patients with brain metastases (56). A small series of patients with progressive brain metastases who failed on RT or surgery plus RT and received treatment with bevacizumab with or without chemotherapeutic agents were reported for breast cancer (57,58), NSCLC (59) and colorectal cancer (60). The ORR of the studies was 33 -100%, and the PFS and OS of patients with breast cancer and brain metastases were 2.8 -9 and 7.8 months, respectively.…”
Section: Brain Metastasesmentioning
confidence: 99%
“…The PASSPORT study of patients with non-small lung cell carcinoma (NSCLC) and nonprogressive brain metastases after RT demonstrated that bevacizumab in addition to chemotherapeutic agents or erlotinib did not induce grade 2 ICH and that bevacizumab can be safely used in patients with brain metastases (56). A small series of patients with progressive brain metastases who failed on RT or surgery plus RT and received treatment with bevacizumab with or without chemotherapeutic agents were reported for breast cancer (57,58), NSCLC (59) and colorectal cancer (60). The ORR of the studies was 33 -100%, and the PFS and OS of patients with breast cancer and brain metastases were 2.8 -9 and 7.8 months, respectively.…”
Section: Brain Metastasesmentioning
confidence: 99%
“…Corticosteroids are widely used for the treatment of brain cancer because they provide relief from symptoms related to intracranial pressure and edema, but their constant use is associated with potentially serious side effects. VEGF receptor inhibitors, due to their antiedema properties, have been investigated as an alternative therapy, firstly in glioblastoma [11] and then in brain metastases [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Best CNS response, was partial in two, stable disease in three, and progression in one patient. Improvement in symptoms and reduction in corticosteroid requirements was reported (37).…”
Section: Angiogenesis In Brain Metastasesmentioning
confidence: 98%